2008
DOI: 10.1111/j.1444-2906.2008.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and complete primary structures of myosin heavy chains from brushtooth lizardfishSaurida undosquamisand wanieso lizardfishS. waniesofast skeletal muscles

Abstract: The complete cDNA sequences encoding predominant types of myosin heavy chain (MYH) in the fast skeletal muscle were determined for brushtooth lizardfish Saurida undosquamis and wanieso lizardfish S. wanieso, which are used as materials for preparing high-quality surimi-based products. The cDNA consisted of 5973 and 5987 bp, respectively, and both encompassed an open reading frame encoding a polypeptide of 1936 amino acid residues. Brushtooth and wanieso lizardfish MYH showed the amino acid sequence identity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…3), confirmed that common carp embryonic MYH emb1 and MYH emb2 both belong to a fast type, whereas MYH emb3 does to a slow/cardiac type. MYH emb1 and MYH emb2 formed a monophyletic clade with zebrafish myhz2 and myhc4 (Xu et al, 2000;Peng et al, 2002;Nihei et al, 2006), and these MYHs formed one group with brushtooth lizardfish MYH Su Fast (Hossain et al, 2008), wanieso lizardfish MYH Sw Fast (Hossain et al, 2008), chum salmon MYH Ok Fast (Ojima et al, 1998), walleye pollack MYH Tc Fast (Togashi et al, 2000), yellowbelly rockcod MYH Nc fast (Gauvry et al, 2000), torafugu MYH M743-2 (Ikeda et al, 2004;Ikeda et al, 2007) and white croaker MYH Pa Fast (Yoon et al, 2000) (see Fig. 3).…”
Section: Mandibular Archmentioning
confidence: 98%
“…3), confirmed that common carp embryonic MYH emb1 and MYH emb2 both belong to a fast type, whereas MYH emb3 does to a slow/cardiac type. MYH emb1 and MYH emb2 formed a monophyletic clade with zebrafish myhz2 and myhc4 (Xu et al, 2000;Peng et al, 2002;Nihei et al, 2006), and these MYHs formed one group with brushtooth lizardfish MYH Su Fast (Hossain et al, 2008), wanieso lizardfish MYH Sw Fast (Hossain et al, 2008), chum salmon MYH Ok Fast (Ojima et al, 1998), walleye pollack MYH Tc Fast (Togashi et al, 2000), yellowbelly rockcod MYH Nc fast (Gauvry et al, 2000), torafugu MYH M743-2 (Ikeda et al, 2004;Ikeda et al, 2007) and white croaker MYH Pa Fast (Yoon et al, 2000) (see Fig. 3).…”
Section: Mandibular Archmentioning
confidence: 98%
“…Based on this background, cDNA encoding a portion of the myosin heavy chain was cloned from fast skeletal muscle of Japanese codling . Phylogenetic analysis of the deduced amino acid sequence of Japanese codling myosin heavy chain revealed that this fish belongs to a group containing white croaker (Pennahia argentatus), walleye pollack (Gadus chalcogrammus), and brushtooth lizardfish (Saurida undosquamis) commonly used as materials for surimi-based products, suggesting that Japanese codling meat is a promising candidate for surimi-based products.…”
Section: Introductionmentioning
confidence: 99%